Living Within the Macrophage: Dimorphic Fungal Pathogen Intracellular Metabolism - Shen, Qian; Rappleye, Chad A. (Frontiers in Cellular and Infection Microbiology, 2020)
Histoplasma and Paracoccidioides are related thermally dimorphic fungal pathogens that cause deadly mycoses (i.e., histoplasmosis and paracoccidioidomycosis, respectively) primarily in North, Central, and South America. Mammalian infection results from inhalation of conidia and their subsequent conversion into pathogenic yeasts. Macrophages in the lung are the first line of defense, but are generally unable to clear these fungi. Instead, Histoplasma and Paracoccidioides yeasts survive and proliferate within the phagosomal compartment of host macrophages. Growth within macrophages requires strategies for acquisition of sufficient nutrients (e.g., carbon, nitrogen, and essential trace elements and co-factors) from the nutrient-depleted phagosomal environment. We review the transcriptomic and recent functional genetic studies that are defining how these intracellular fungal pathogens tune their metabolism to the resources available in the macrophage phagosome. In addition, recent studies have shown that the nutritional state of the macrophage phagosome is not static, but changes upon activation of adaptive immune responses. Understanding the metabolic requirements of these dimorphic pathogens as they thrive within host cells can provide novel targets for therapeutic intervention.